The dark side of the earth : Russia's short-lived victory over totalitarianism - Zygarʹ, Mikhail, 1981- (Scribner, 2025)
"From "one of Russia's smartest and best-sourced" (The New York Times) reporters comes a gripping and urgent exploration of why the Soviet Union's collapse was incomplete and the Cold War was never over-revealing the resurgence of imperialism in Russia and its current implications for the war in Ukraine. Russian-born journalist Mikhail Zygar was ten years old when the Soviet Union collapsed. Now, after nearly ten years of research, he offers a timely and compelling new approach on Russian history-one that rewrites everything we thought we knew about the fall of the Soviet Union-and argues that its ending is yet to come. Starting with the historic launch of the first human into space in April 1961, Zygar unravels a dramatic story of resistance, resilience, and resurgence that led to the Soviet Union's dissolution-and the echoes of its legacy today. Zygar conducted several hundred exclusive interviews with key figures, including Soviet President Mikhail Gorbachev, first presidents of the independent post-Soviet republics, the last first secretaries of these republics, and leaders of independence movements within them, as well as Western politicians and diplomats who were witnesses to and participants in those events. He dives into the struggles and triumphs of figures like Andrei Sakharov, Alexander Solzhenitsyn, and Vladimir Vysotsky, whose defiance of totalitarianism is both inspiring and deeply relevant. Zygar explains how the "victory" over the Soviet Empire may have been short-lived, as today's Russian regime maintains its imperial ambitions. A must-read for anyone looking to understand the origins of modern Russian fascism, The Dark Side of the Earth explores how imperial and nationalist ideas developed during the Soviet era and eventually gave rise to the current Putinist ideology. Zygar's work is uniquely powerful-fueled by his personal ties to the Soviet era, access to historical archives, and interviews that crack open hidden truths, including several with individuals who had never before spoken on the record. More than a history lesson, The Dark Side of the Earth is a call to action and a testament to the enduring fight for truth and freedom. Zygar urges us to confront the narratives we've accepted and rethink how we face oppression today. Bold, brilliant, and deeply human, this is a story that demands to be heard"-- Provided by publisher.